Characterizing the role of SLC3A2 in the molecular landscape and immune microenvironment across human tumors - He, Jiajun; Liu, Dong; Liu, Mei; Tang, Rong; Zhang, Dongqing (Frontiers in Molecular Biosciences, 2022)
Abstract Background: Induction of ferroptosis in human tumors has become a potential strategy to improve the prognosis of patients even in those with chemotherapeutic resistance. xCT complex is a major target for ferroptosis induction, comprising of SLC7A11 and SLC3A2. The role of SLC7A11 in cancer has been studied widely in recent years, however, related researches for its partner SLC3A2 are still rare. Methods: Bulk transcriptome, single-cell sequencing and immunohistochemical staining were analyzed to explore the expression distribution. Clinical outcomes were referred to uncover the relationship between SLC3A2 expression and patients’ prognosis. Immune cell infiltration was evaluated by multiple deconvolution algorithms. The effect of SLC3A2 on the proliferation and drug resistance of cancer cell-lines was evaluated by DEPMAP. Results: Upregulated SLC3A2 may have an adverse effect on the survival of several cancer patients such as lower grade glioma and acute myeloid leukemia. SLC3A2 expression is indispensable for multiple cell-lines’ proliferation, especially for ESO51 (a cell-line for esophageal cancer). In addition, SLC3A2 expression level was related to the remodeling of immune microenvironment in cancers and some immune check-point like PD-1 and PD-L1, which were potential therapeutic targets in many distinct cancers. Conclusion: Our study systematically elucidated the role of SLC3A2 in the survival of cancer patients and potential immunotherapeutic response. Future research into the biological mechanism could further help with targeted treatment for cancer patients.